1970
DOI: 10.2307/1942440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Cutting and Herbicide Treatment on Nutrient Budgets in the Hubbard Brook Watershed‐Ecosystem

Abstract: Abstract. All vegetation on Watershed 2 of the Hubbard Brook Experimental Forest was cut during November and December of 1965, and vegetation regrowth was inhibited for two years by periodic application of herbicides. Annual stream-flow was increased 33 em or 39% the first year and 27 em or 28% the second year above the values expected if the watershed were not deforested.Large increases in streamwater concentration were observed for all major ions, except NH 4 +, S0 4 = and HC0 3 -, approximately five months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
533
8
11

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,075 publications
(597 citation statements)
references
References 36 publications
38
533
8
11
Order By: Relevance
“…Indeed, we found negligible concentrations of NO 3 Ϫ and NH 4 ϩ in streamwater and snowmelt in burned areas of Yellowstone (72), and nutrient concentrations in Yellowstone's lakes were not elevated after the 1988 fires (73). Thus, postfire losses of N may be minimal in this ecosystem, in contrast to large nitrate losses after disturbances in the more fertile, eastern deciduous forests (10,74). Our data suggest that the firedominated conifer forests of the GYE are highly conservative for N, and the important N sinks in this landscape likely shift from microbial immobilization to plant uptake as postfire succession proceeds.…”
Section: Enhanced Microbial Immobilization Of Nhmentioning
confidence: 69%
“…Indeed, we found negligible concentrations of NO 3 Ϫ and NH 4 ϩ in streamwater and snowmelt in burned areas of Yellowstone (72), and nutrient concentrations in Yellowstone's lakes were not elevated after the 1988 fires (73). Thus, postfire losses of N may be minimal in this ecosystem, in contrast to large nitrate losses after disturbances in the more fertile, eastern deciduous forests (10,74). Our data suggest that the firedominated conifer forests of the GYE are highly conservative for N, and the important N sinks in this landscape likely shift from microbial immobilization to plant uptake as postfire succession proceeds.…”
Section: Enhanced Microbial Immobilization Of Nhmentioning
confidence: 69%
“…S1 and S2). This approach has been commonly used in large-scale ecosystem manipulations such as the Hubbard Brook Ecosystem Study (47). Results from an earlier soil-warming experiment confirmed that the soil disturbance associated with the installation of heating cables has had no effect on soil temperatures or soil respiration and only minor and variable impacts on soil moisture, net nitrogen mineralization (Fig.…”
Section: Methodsmentioning
confidence: 76%
“…Golladay et al [34] and Arthur et al [35] found increases in nitrogen and phosphorus export in logged catchments in Appalachia but minor differences in calcium, potassium, or sulfate concentrations between logged and undisturbed watersheds. Likens et al [36] actually found sulfate concentrations to decrease following clear-cutting and experimental suppression of forest growth by herbicides.…”
Section: Preceding Causationmentioning
confidence: 97%